Relationship Between Performance of Brand Ambassador Oppo Advertising and Oppo Advertising Message Level on Oppo Buying Interest Oppo Product - Muhammad Luthfi Razan; Djoko Setyabudi, S.Sos, MM (Interaksi Online, 2017)
Oppo is one of the smartphone manufacturers in Indonesia, Oppo uses brand ambassador as one of the strategies in its iklanya, Oppo using brand majority of celebrities from celebrities, Oppo brand ambassador is expected to be a draw for the audience who saw the advertisement Oppo, so that will help the audience In understanding the advertising message submitted by brand ambassador, after the audience understands the advertising message is conveyed it will stimulate the interest of buying audience of Oppo products. The purpose of this study is to determine the relationship of Oppo brand ambassador advertising performance and the level of understanding of Oppo's advertising messages to the buying interest of Oppo products. Theory used in this research is Response Cognitive Theory which explains the relationship between the performance of Brand Ambassador Oppo Advertising on the Oppo Advertising Message Level Understanding, Elaboration Likehood Theory which explains the Relationship Between the Performance of Brand Ambassadors of Oppo Advertising on Oppo's buying interest. The population of this study is adolescents aged 18-25 years who became the target target of Oppo and samples taken as many as 50 people with conventional sampling techniques. In the hypothesis test, the authors used the correlation analysis of kendall tau_b. Testing data that is done by using program SPSS 23, there is Between Performance of Brand Ambassador Advertising Oppo (X1) to the interest of buying product of Oppo (Y) with significance value is 0,862 is> 0,50 which means there is relation and Relationship Level understanding of advertising message Oppo (X2) to the buying interest of Oppo (Y) product with significance value is 0,751, proving hypothesis H1 that there is positive relation and hypothesis H2 there is also positive relationship.